Effects of Aspirin and Prednisone on Platelet Function and Thromboxane Synthesis in Healthy Dogs - Thomason, John M.; Mooney, Allison P.; Price, Joshua M.; Whittemore, Jacqueline C. (Frontiers in Veterinary Science, 2019)
Glucocorticoid administration is a risk factor for thromboembolism in hypercoagulable dogs, and it is unknown if aspirin counteracts glucocorticoid-induced hypercoagulability. The objective was to determine the effects of sustained aspirin and prednisone administration on platelet function and thromboxane synthesis. Our hypothesis was that aspirin would consistently inhibit platelet function and thromboxane synthesis when administered with or without prednisone. In 24 healthy dogs, platelet aggregometry and urine 11-dehydro-thromboxane-B2 (11-dTXB2)-to-creatinine ratios were measured on days 0, 14, and 28. Dogs were administered placebos, aspirin (2 mg/kg/d), prednisone (2 mg/kg/d), or prednisone/aspirin combination therapy PO for 28 days in a randomized double-blinded study. Aspirin response was based on a >25% reduction in platelet aggregation compared to pre-treatment values. Results were compared using mixed model, split-plot repeated measures ANOVAs. P<.05 was considered significant. AUC differed significantly by time (F[2,40] = 10.2, P<.001) but not treatment or treatment-by-time. On day 14, 2 dogs were aspirin responders (aspirin, 1; placebo, 1). On day 28, 3 dogs were aspirin responders (aspirin, 2; prednisone/aspirin, 1). Urine 11-dTXB2-to-creatinine ratios differed significantly by group (F[3,20] = 3.9, P=.024) and time (F[2,40] = 8.7, P<.001), but not treatment-by-time. Post-hoc analysis revealed significant differences between aspirin and placebo groups (P=.008), aspirin and prednisone/aspirin groups (P=.030), and placebo and prednisone groups (P=.030). In healthy dogs, sustained aspirin, prednisone, and combination therapy do not inhibit platelet aggregation, and when used as individual therapies, aspirin and prednisone decreased thromboxane synthesis. Additional studies using varied platelet function methodologies in hypercoagulable dogs are necessary.